Cost accounting for environmental safety - O. Kovalenko (Вестник университета)
The article describes the main approaches to cost accounting for environmental security, the analysis of methods of cost accounting, proposals for the organization of accounting for the item "Environmental protection measures", systematizing the cost of measures for environmental protection aimed at co-storage and restoration of natural environment, rational use and vosproizvel of natural resources